Economies of scale in finishing cattle - Porter, R.W.; Jones, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The results of this study indicate that farmer-feeders who finish as few as 700 head per year can compete with the large commercial feedlots from a cost perspective. The lack of a sophisticated feed mill does not prevent the farmer-feeder from being competitive with the large commercial feedlots in feed costs. This might be explained by the farmer feeder producing much of the feed, which reduces transportation and transaction costs. The farmer-feeder has non-feed costs that average 64% more than those of the large commercial feedlots. The significantly greater costs for depreciation, repairs, and maintenance may be explained by having fewer numbers of cattle to spread the equipment over. As evidenced by the rapid structural change in the cattle feeding industry, it is not easy for the relatively smaller-scale farmer-feeder operation to compete in the cattle feeding industry. This cost-comparison study indicates that it is possible for well managed small-scale feeders to be competitive from an overall cost perspective.
Keywords: Beef; Economies; Finishing cattle